2000
DOI: 10.1093/geront/40.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Two Transitions in Daughters' Caregiving Careers

Abstract: Daughters and daughters-in-law of presently unmarried elders were studied longitudinally, and the data were analyzed to determine how two transitions in caregiving status affected the women of the younger generation. One transition compared noncaregivers who had become caregivers 1 year later ("caregiving entrants," n = 33) with continuing noncaregivers (n = 56) and with veteran continuing caregivers (n = 78) over the same period. The second transition followed Time 1 new caregivers as they became "new veteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
125
3
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(137 citation statements)
references
References 22 publications
6
125
3
3
Order By: Relevance
“…14,27 A few studies followed samples of noncaregivers until they became caregivers and then compared them with those who didn't take on this role. 16,22,28,29 Both Burton and colleagues and Hirst demonstrated that moving into a demanding caregiving role-providing assistance with basic ADLs for 20 hours or more per week-resulted in increased depression and psychological distress, impaired self-care, and poorer self-reported health. 16,22 A few studies have examined the effects of making the transition out of the caregiving role because the patient improves, enters an institution, or dies.…”
Section: Transitions Into and Out Of Caregivingmentioning
confidence: 99%
“…14,27 A few studies followed samples of noncaregivers until they became caregivers and then compared them with those who didn't take on this role. 16,22,28,29 Both Burton and colleagues and Hirst demonstrated that moving into a demanding caregiving role-providing assistance with basic ADLs for 20 hours or more per week-resulted in increased depression and psychological distress, impaired self-care, and poorer self-reported health. 16,22 A few studies have examined the effects of making the transition out of the caregiving role because the patient improves, enters an institution, or dies.…”
Section: Transitions Into and Out Of Caregivingmentioning
confidence: 99%
“…In this study revised caregiver appraisal scale [13] was applied to assess caregiver appraisal. There were two types of items.…”
Section: Caregiver Appraisalmentioning
confidence: 99%
“…In his study, the negative effect on life satisfaction becomes insignificant when individual fixed-effects are taken into account. Lawton et al (2000) also find very little evidence that becoming a caregiver or caring over a long period worsens the caregiver's well-being.…”
mentioning
confidence: 91%
“…Perceived social support (+), self-esteem (+), informal care hours (-), and burden (-) have a significant influence on caregivers' mental health Cohen et al (2002) N=289, subsample from the Canadian Study of Health and Aging (1996, C) Stepwise regression, caregiving relationship, residency, care receiver, caregiver age, and gender 73% of caregivers perceive at least one positive outcome of caregiving, which positively affects mental and physical health Dujardin et al (2011) Census data from Britain (N=1,361,222) (1991-2000, L) Logit, care intensity, care duration, care location, and relationship Starting or leaving intense caregiving is associated with high psychological distress Lawton et al (2000) N=634, Volunteer female sample (1990-1994, C) MANOVA, comparison of new and veteran caregivers…”
mentioning
confidence: 99%